PENGARUH KEPEMIMPINAN TRANSAKSIONAL, BUDAYA ORGANISASI, DAN DUKUNGAN SOSIAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN PT LONG RICH - Indah Fatma Rosmayanti; Celsya Wardah Tulzannah; Aji Rizki Ramadhan; Angga Prayogi Brilyanto (STKIP Subang, 2026)
Organizational Citizenship Behavior (OCB) is an important factor in improving organizational effectiveness, particularly in manufacturing companies that rely on teamwork to achieve production targets. However, employees may still show limited initiative to assist their coworkers beyond formal job responsibilities, which can hinder production efficiency. This study aims to analyze the influence of transactional leadership, organizational culture, and social support on Organizational Citizenship Behavior (OCB) among employees of PT Long Rich. This study employed a quantitative approach using a purposive sampling technique involving 130 employees of PT Long Rich. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination with IBM SPSS. The findings indicate that transactional leadership, organizational culture, and social support have a positive and significant effect on Organizational Citizenship Behavior (OCB). Among the independent variables, social support was found to be the most dominant factor influencing OCB. Simultaneously, the three variables explained 55.2% of the variance in Organizational Citizenship Behavior. The findings provide practical implications for manufacturing companies in strengthening social support, fostering a positive organizational culture, and implementing effective leadership practices to enhance employees' Organizational Citizenship Behavior.